2010
DOI: 10.1007/s10637-010-9388-4
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1, multicenter, open-label study of the safety of two dose levels of a human monoclonal antibody to human αv integrins, intetumumab, in combination with docetaxel and prednisone in patients with castrate-resistant metastatic prostate cancer

Abstract: Intetumumab was generally safe and well tolerated in combination with docetaxel, with a higher incidence of TEAEs in the 10 mg/kg dose cohort. The efficacy of 10 mg/kg intetumumab in combination with docetaxel appears to warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…We have previously shown that intetumumab is a potential radiation sensitizer when used in combination with fractionated radiation therapy in human cancer xenograft models in nude mice (5). Data from two multicenter clinical phase I studies in patients with advanced solid tumors have shown that intetumumab was safe and well tolerated either alone or in combination with docetaxel (6,7). Intetumumab is now in phase II clinical trials for the treatment of a variety of malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that intetumumab is a potential radiation sensitizer when used in combination with fractionated radiation therapy in human cancer xenograft models in nude mice (5). Data from two multicenter clinical phase I studies in patients with advanced solid tumors have shown that intetumumab was safe and well tolerated either alone or in combination with docetaxel (6,7). Intetumumab is now in phase II clinical trials for the treatment of a variety of malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…14 Phase I clinical trials have been conducted, showing that it is well tolerated in patients with advanced solid tumors 17 and in hormone-refractory prostate cancer patients when administered with docetaxel and prednisone. 18 …”
mentioning
confidence: 99%
“…Other integrin inhibitors that have been studied in clinical trials in prostate cancer include cilengitide, intetumumab, and MK-0429 (36)(37)(38)(39)(40). These agents target various av integrins: cilengitide, integrins avb3 and avb5 (37); intetumumab, av integrins (38); and MK-0429, integrin avb3 (40).…”
Section: Discussionmentioning
confidence: 99%
“…These agents target various av integrins: cilengitide, integrins avb3 and avb5 (37); intetumumab, av integrins (38); and MK-0429, integrin avb3 (40). Both cilengitide and intetumumab were well tolerated, but there was no evidence of activity in phase II trials of these agents (36)(37)(38)(39). MK-0429 caused a reduction in bone turnover, leading the authors to hypothesize that it may have a role in the treatment of metabolic bone disease (40).…”
Section: Discussionmentioning
confidence: 99%